PIRANHA – Hunter of Idle Resources - Birkenheuer, Georg; Hagelweide, Wilke; Hagemeier, Björn; Japs, Viktor; Keller, Matthias; Mayr, Nikolas; Meyer, Jan; Schumacher, Tobias; Voß, Kerstin; Zajac, Markus (Proc. GI Informatiktage)

Glycaemic index and glycaemic load in the diet of healthy schoolchildren: trends from 1990 to 2002, contribution of different carbohydrate sources and relationships to dietary quality. - Buyken, Anette; Dettmann, W; Kersting, M; Kroke, A (Br J Nutr)

Predictive simulation of nanoparticle precipitation based on the population balance equation - Schwarzer, Hans-Christoph; Schwertfirm, Florian; Manhart, Michael; Schmid, Hans-Joachim; Peukert, Wolfgang (Chemical Engineering Science)
Nanoparticle precipitation is an interesting process to generate particles with tailored properties. In this study we investigate the impact of various process steps such as solid formation, mixing and agglomeration on the resulting particle size distribution (PSD) as representative property using barium sulfate as exemplary material. Besides the experimental investigation, process simulations were carried out by solving the full 1D population balance equation coupled to a model describing the micromixing kinetics based on a finite-element Galerkin h-p-method. This combination of population balance and micromixing model was applied successfully to predict the influence of mixing on mean sizes (good quantitative agreement between experimental data and simulation results are obtained) and gain insights into nanoparticle precipitation: The interfacial energy was identified to be a critical parameter in predicting the particle size, poor mixing results in larger particles and the impact of agglomeration was found to increase with supersaturation due to larger particle numbers. Shear-induced agglomeration was found to be controllable through the residence time in turbulent regions and the intensity of turbulence, necessary for intense mixing but undesired due to agglomeration. By this approach, however, the distribution width is underestimated which is attributed to the large spectrum of mixing histories of fluid elements on their way through the mixer. Therefore, an improved computational fluid dynamics-based approach using direct numerical simulation with a Lagrangian particle tracking strategy is applied in combination with the coupled population balance–micromixing approach. We found that the full DNS-approach, coupled to the population balance and micromixing model is capable of predicting not only the mean sizes but the full PSD in nanoparticle precipitation.

Evolution of the fractal dimension for simultaneous coagulation and sintering - Schmid, Hans-Joachim; Al-Zaitone, Belal; Artelt, Christian; Peukert, Wolfgang (Chemical Engineering Science)
Simulation results on the evolution of aggregate structure in aerosol processes with coagulation and sintering as the dominant mechanisms are presented. A model for simulation of the three-dimensional morphology of nano-structured aggregates formed by concurrent coagulation and sintering is applied. The model is based on a stochastic diffusion controlled cluster–cluster aggregation algorithm and sintering is modeled as a successive overlapping of spherical primary particles, which are allowed to grow in order to maintain mass conservation. This leads to computer simulated structured aggregates which are then subject to evaluation. Two different methods to determine the fractal dimension are presented which give comparable results. It is shown that even very small particles show the same fractal behavior. Furthermore, equilibrium structures assuming a constant ratio of the characteristic collision time to the characteristic fusion time are considered as well as the kinetics of structural changes due to a change in the ambient conditions.

On the impact of accessible surface and surface energy on particle formation and growth from the vapour phase - Artelt, C.; Schmid, Hans-Joachim; Peukert, W. (Journal of Aerosol Science)
This work investigates effects of reduced accessible surface area of aggregate particles and surface energy on titania particle formation and growth. It is taken into consideration that surface-related growth mechanisms, i.e. surface reaction and condensation, are limited to the fraction of the surface area of primary particles which is exposed to the collision with single molecules. Surface energy data determine the critical particle size with respect to evaporation and values are varied within the published range. This implies to develop a model which considers “surface shielding” and accounts for the formation of stable clusters from a supersaturated vapour due to nucleation and condensation besides considering the generation of monomers due to chemical reaction, growth due to surface reaction, agglomeration and sintering. Taking the accessible surface area into account is found out to be especially important if agglomerates contain a large number of primary particles or if agglomerate structure is rather compact. In this case, precursor consumption and primary particle growth turn out to be significantly retarded. Surface energy data are shown to be decisive with respect to the thermodynamic barrier to the formation of particles, thus to active particle formation and growth mechanisms, besides affecting sintering kinetics. Elevated surface energy data typically retard precursor consumption and favour primary particle growth.

Unscharfe Break-Even-Analyse bei Einproduktproduktion - Betz, Stefan

Nonlinear Reformulation of Heisenberg's Dynamics - Ziegler, Martin; Fuchssteiner, Benno (International Journal of Theoretical Physics)

Interessen, Selbstkonzepte und Kompetenzen. Untersuchungen zum Lernen von Mathematik bei Grundschulkindern - Hellmich, Frank

Lehren und Lernen nach IGLU – Beiträge zum Grundschulunterricht

Unscharfe Produktionsprogrammplanung bei Alternativproduktion - Betz, Stefan